Examining changes to food and beverage availability and marketing in a low-income community after the opening of a new supermarket. Issue 17 (3rd December 2021) - Singleton, Chelsea R; Li, Yu; Zenk, Shannon N; Powell, Lisa M
Abstract: Objective: In 2016, a Whole Foods Market© opened in the Englewood community of Chicago, IL – a predominately low-income African American community. This study aimed to examine changes to food and beverage availability and marketing in Englewood's existing food stores after the opening of this supermarket. Design: Quasi-experimental study. Setting: Two low-income African American communities in Chicago, IL. Participants: Fieldworkers audited all small grocery and limited service stores (e.g. convenience stores, liquor stores and dollar/discount stores) located within one-square mile of the new supermarket and a one-square mile area of a demographically comparable community that also lacked a supermarket. Stores were audited before (2016) and after (2017 and 2018) the supermarket opened. Results: Of the 78 stores audited at baseline, 71·8 % were limited service stores and 85·9 % accepted Supplemental Nutrition Assistance Program (SNAP) benefits. Overall, the availability of healthy food and beverage options in nearby small stores was low at baseline and both follow-up periods. Difference-in-difference regression models revealed a significant increase in: (1) the percentage of stores in the intervention community (i.e. Englewood) offering regular cheese and promoting salty snacks at check-out from 2016 to 2017; and (2) the percentage of stores in the comparison community with interior store promotions for other sweetened beverages from 2016 to 2018. Conclusions: Minimal changes in food and beverage availability and marketing occurred 1 and 2 years after the opening of a new supermarket. However, the wide range of staple food items offered by the supermarket expanded healthy food retail in Chicago's Englewood community.